A SYSTEMATIC REVIEW TO ASSESS THE EFFECTIVENESS OF WEB BASED TRAINING VIDEO FOR LAPAROSCOPY SURGERY - Egedovo, Alfred; Ho, Yik-Hong; Larkins, Sarah; Mushuya, Chrispen (International Journal of Research -GRANTHAALAYAH, 2017)
Background: Surgical training for generations has followed the example of an apprenticeship model propagated by William Halsted; teaching method of “see one, do one, teach one”. 1-3Teaching of surgical trainee is time consuming and costly in the operating room when it involves a procedure,4, 5 and the surgical skills acquired from operating room are of variable effectiveness because of the learning curve.6, 7 The objective of this review is to determine if web-based training video (WBTV) is effective to supplement and /or replace the standard surgical training model (SLT). However, the value of this modality for trainees with or no laparoscopic experience is unknown. Study Hypothesis: Multimedia or Web-based training video (WBTV) learning is equivalent to conventional teaching (Standard surgical training-SLT) in improving scores in cognitive surgical skills. Search Method:Randomized clinical trials addressing this issue were identified from The Cochrane Library trials register, Medline, Embase, Science Citation Index Expanded, grey literature and reference lists and other databases. The Cochrane Central Register of Controlled Trials: search was narrowed to Issue of 6 of 12, June 2014. Included studies were randomized controlled trials (RCTs) assessing any training technique using at least some elements of surgical simulation, which reported measures of surgical task performance. The Cochrane search yielded one relevant article.8 In the MEDLINE search, the medical Subject Heading (MeSH) was used to search for; Surgical stimulation, surgical training, “Web-based training” and “online education or teaching, training, internet, multimedia teaching” (retrieved articles 78, relevant articles 50) and the headings “Laparoscopy” and “education” (retrieved 103, relevant 91) other provisional abstract (review 3). I focused the search on articles published from 1990 onwards, and I limited it to articles published in English. I did not include case reports and data from abstracts in data synthesis. All of the identified articles were examined for relevance. Retrieved studies were screened for duplication, and additional studies were identified using a manual search of the reference list of the relevant included articles. Since my review focused on Web-based training video effectiveness for teaching laparoscopic surgery techniques, my search strategies was limited to identifying articles focusing on surgical education. Selection Criteria:I included all randomised clinical trials comparing Web-based model trainers versus other forms of training including standard laparoscopic training and supplementary animal model training use for teaching surgical trainees with or no laparoscopic experience. I also included trials comparing different methods of simulation surgical training. Results: Thirty RCTs with 831 participants were included, although the quality of the RCTs was often poor. The Web-based training video (WBTV) had one RCTs, the RCT had four intervention groups, they were groups multimedia(WBTV) training, Practical Training (Standard training, Multimedia (WBTV) plus practical training and none of the trainings had different skills but all participants were homogeneous with the same basic skills on laparoscopic cholecystectomy. The result was that multimedia –based (WBTV) training improved surgical performance of Laparoscopic cholecystectomy in a pelvic –trainer significantly when used alone or as combination training. While Virtual reality simulation had shown better results than no training at all, but had no evidence of superiority over standard training practised. When it is done purposefully or video box simulation based on operative performance. Video simulation did not show consistently better results than groups with no training at all, and there were not enough data to determine if video simulation was better than standard training or the use of models. Model simulation may have been better than standard training. Two trials (mostly with a high risk of bias) involving 110 participants were included in this review. In trainees without surgical experience, WBTV training decreased the time taken to complete a task, increased accuracy and decreased errors compared with no training. In the same participants, WBTV training was more accurate than Standard practical training. In participants with laparoscopic experience practical training plus Web-based video training, WBTV training resulted in a greater reduction in operating time, error and unnecessary movements than standard laparoscopic training. In these participants, the composite performance score was better in the WBTV group than the practical group (standard). Conclusion: WBTV can supplement standard surgical training. However the quality is poor, It is at least as effective as no standard training in supplementing standard laparoscopic training. While there may be compelling reasons to reduce reliance on patients, cadavers, and animals for surgical training, none of the methods of simulated training has yet been shown to be better than other forms of surgical training.